Immigration quotas and anti-immigration attitudes: An evaluation of Swiss migration policy - Qingyang Lin (Graduate Institute of International and Development Studies, 2022)
Switzerland implemented an immigration quota system to manage the inflow of immigration between 1970 and 2002. This paper adopts a difference-in-difference strategy taking advantage of subnational variations in the implementation of the quota system to evaluate this migration policy. An instrument variable of antiimmigration attitudes is used to address the potential endogeneity issue. The author finds that the immigration quota system slowed down the growth of foreign population in Switzerland, but had no impact on unemployment. Moreover, such immigration restriction lowered the average skill level of the Swiss population which in turn hurt the productivity of the Swiss economy.
Keywords: F22; J21; J24; J61; K37; 330; Migration; Anti-Immigration Attitudes; Unemployment; Labor Skills